Effect of Tween 80 on glucosyltransferase production in Streptococcus mutans. - Umesaki, Y (1977)
Glucan production from sucrose by Streptococcus mutans OMZ 176 was stimulated approximately threefold in the presence of 0.1% Tween 80. When OMZ 176 was grown in a medium containing glucose, the glucosyltransferase level in the medium was also increased about fivefold in the presence of 0.1% Tween 80. The glucosyltransferase level increased in proportion to the logarithm of the concentration of Tween 80 in the glucose medium. Tween 80 affected neither bacterial growth nor the activity of glucosyltransferase. The appearance of glucosyltransferase in the glucose medium was inhibited immediately by chloramphenicol and actinomycin D and, after a lag, by rifampin as well. It was observed that the fatty acid composition of the cells grown with Tween 80 was altered. These results suggest that Tween 80 stimulates glucosyltransferase synthesis either directly, or indirectly by promoting glucosyltransferase secretion.